2017
DOI: 10.1063/1.4978574
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight dependence of the intrinsic size effect on Tg in AAO template-supported polymer nanorods: A DSC study

Abstract: Many studies have established a major effect of nanoscale confinement on the glass transition temperature (T) of polystyrene (PS), most commonly in thin films with one or two free surfaces. Here, we characterize smaller yet significant intrinsic size effects (in the absence of free surfaces or significant attractive polymer-substrate interactions) on the T and fragility of PS. Melt infiltration of various molecular weights (MWs) of PS into anodic aluminum oxide (AAO) templates is used to create nanorods suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 95 publications
5
28
0
Order By: Relevance
“…T g values of bulk and molecularly confined polymers were measured by flash differential scanning calorimetry (flash‐DSC) at a heating rate of 8000 K s −1 ( Figure ). Molecular confinement of PS in the nanocomposite decreases T g of the polymer for all the samples investigated, consistent with previous reports on molecularly confined (but not hyperconfined) polymers in cylindrical pores showing decreased T g and enhanced segmental mobility . We note that the T g values of bulk PS we measured on PS powder are higher than what have been reported using conventional DSC (105–107 °C) because the heating rate employed in our flash‐DSC measurement is six orders of magnitude higher than what is used in conventional DSC.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…T g values of bulk and molecularly confined polymers were measured by flash differential scanning calorimetry (flash‐DSC) at a heating rate of 8000 K s −1 ( Figure ). Molecular confinement of PS in the nanocomposite decreases T g of the polymer for all the samples investigated, consistent with previous reports on molecularly confined (but not hyperconfined) polymers in cylindrical pores showing decreased T g and enhanced segmental mobility . We note that the T g values of bulk PS we measured on PS powder are higher than what have been reported using conventional DSC (105–107 °C) because the heating rate employed in our flash‐DSC measurement is six orders of magnitude higher than what is used in conventional DSC.…”
Section: Resultssupporting
confidence: 91%
“…Increasing M w from 50 to 426 kDa makes Δ T g of surface‐hydroxylated nanocomposite significantly more negative but essentially does not affect Δ T g of untreated nanocomposite. Askar et al have shown that molecular confinement (but not hyperconfinement) of PS in the cylindrical nanopores of anodic aluminum oxide (AAO) templates makes Δ T g negative, and Δ T g becomes more negative with increasing M w for the same pore size, which is consistent with the Δ T g − M w relationship in the case of surface‐hydroxylated nanocomposite in our work. Such a consistency is likely due to the fact that the interaction between PS and AAO surface is comparable to the interaction between PS and the hydroxylated surface.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, several recent studies have reported differences in confinement behavior associated with chain length, stiffness, entanglements, and chain architecture that are unexpected given the primarily enthalpic understanding developed over the years. This suggests that entropic effects may also play a modifying role in understanding confinement effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ellipsometry, capillary dilatometry, and X‐ray reflectivity require relatively flat, continuous films to accurately measure T g . While DSC has been used to study 2D‐confined (where two dimensions are restricted to the nanoscale) polymer systems through anodized aluminum oxide (AAO) template‐supported nanorods and nanotubes, sample geometry and interfacial interactions were somewhat limited by template constraints. Additionally, these techniques do not enable location‐specific measurements in the presence of a free surface without costly and time‐intensive scattering and reflectivity studies.…”
Section: Fluorescence To Measure Tg and Physical Aging In Single‐compmentioning
confidence: 99%